Pengaruh Pola Karier, Motivasi Pegawai, Team Building Dan Kepemimpinan Terhadap Kinerja Pegawai PT. PLN (Persero) Kantor Wilayah Suluttenggo - Rachmad, Rizal (JURNAL RISET BISNIS DAN MANAJEMEN)
The purpose of this researh is to find the relationship between Career's Path, Employee's Motivation, Team Building and Leadership towards Employee's Performance in PT PLN (Persero) Wilayah Suluttenggo. Sample choosen for this research is 65 employees in Kantor Wilayah Suluttenggo. Sample was generated using stratified random sampling because thepopulation consists of several job's position, grade and education background. Collected data result then processed with multiple regression analysis method using SPSS. The result ofthis study shows that Employee's Motivation and Team Building have a positif significant influence toward Employee's Performance. The multiple regression analysis generate theequation as such : Y=2,636 – 0,058 X1 + 0,667 X2 + 0,278 X3 – 0,135 X. Independent variable has a contribution of 59% towards Employee Performance variable, whereas 41% is influenced by variables other than those that being studied.Keywords : Career Path, Motivation, Team Building, Leadership, Performance.